3D micro-porous conducting carbon beehive by single step polymer carbonization for high performance supercapacitors: the magic of in situ porogen formation - Puthusseri, Dhanya; Aravindan, Vanchiappan; Madhavi, Srinivasan; Ogale, Satishchandra (Energy & Environmental Science, 2014)
We report non-templated synthesis of interconnected microporous carbon (IMPC) sheets having beehive morphology by direct pyrolysis of poly(acrylamide-co-acrylic acid) potassium salt in inert atmosphere without any activation. The presence of the alkali metal in the selected polymer precursor results in a high specific surface area of 1327 m(2) g(-1). Importantly, 80% of the pore volume is contributed by micropores with pore size ranging from 1-2 nm which is ideal for use as an electrode for supercapacitors. Whereas the rest of the surface area was contributed by a small fraction of mesopores and macropores due to the interconnected structure. The presence of three different types of pores make the material ideal for supercapacitor electrodes. IMPC was tested as an electrode in both aqueous and non-aqueous supercapacitors. All the aqueous measurements were done in 1 M H2SO4 solution with a potential window 1 V. A specific capacitance of 258 F g(-1) was realized at a constant charge-discharge current of 0.5 A g(-1) and it maintained at a value of 150 F g(-1) at 30 A g(-1). A long cycle stability of 90% capacitance retention was observed after 5000 charge-discharge cycles at a current density of 2 A g(-1). At the highest power density 13 600 W kg(-1) the energy density was found to be 3.1 W h kg(-1). Non aqueous performance was tested in the presence of 1 M LiPF6 in ethylene carbonate-di-methyl carbonate with 5 mg active material loading. A specific capacitance of 138 F g(-1) was obtained at a current density of 0.25 A g(-1) and it retained at a value of 100 F g-1 at 10 A g(-1). The material can deliver an energy density of 31 W h kg(-1) at its highest power density of 11 000 W kg(-1) in a two electrode system based on active material loading.

From waste paper basket to solid state and Li-HEC ultracapacitor electrodes: a value added journey for shredded office paper - Puthusseri, Dhanya; Aravindan, Vanchiappan; Anothumakkool, Bihag; Kurungot, Sreekumar; Madhavi, Srinivasan; Ogale, Satishchandra (Small, 2014)
Hydrothermal processing followed by controlled pyrolysis of used white office paper (a globally collectable shredded paper waste) are performed to obtain high surface area carbon with hierarchical pore size distribution. The BET specific surface area of such carbon is 2341 m 2 g(-1). The interconnected macroporous structure along with the concurrent presence of mesopores and micropores makes the material ideal for ultracapacitor application. Such waste paper derived carbon (WPC) shows remarkable performance in all solid-state supercapacitor fabricated with ionic liquid-polymer gel electrolyte. At room temperature, the material exhibits a power density of 19 000 W kg(-1) with an energy capability of 31 Wh kg(-1). The Li-ion electrochemical capacitor constructed using WPC as cathode also shows an excellent energy storage capacity of 61 Wh kg(-1)

Improving the energy density of Li-ion capacitors using polymer-derived porous carbons as cathode - Puthusseri, Dhanya; Aravindan, Vanchiappan; Madhavi, Srinivasan; Ogale, Satishchandra (Electrochimica Acta, 2014)
High energy density Li-ion hybrid electrochemical capacitors (Li-HEC) are fabricated with 3 D architectured high surface area porous carbon (HSPC) derived from the poly(acrylamide-co-acrylic acid) potassium salt in a single step without any activating agent. The obtained HSPC exhibits high specific surface area of 1490 m(2) g(-1) and characterized with several analytical techniques. Li-HEC is fabricated with insertion type Li4Ti5O12 anode by adjusting the mass balance based on the single electrode performance with Li. The Li-HEC delivered the maximum energy density of similar to 55 Wh kg(-1), which is much higher than commercially available activated carbon (similar to 36 Wh kg(-1)). Further HSPC based Li-HEC delivered excellent cycleability and rendered similar to 87% of initial value after 2000 cycles. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: energy density; Li-ion hybrid electrochemical capacitors; non-aqueous; porous carbon

Indanthrone derived disordered graphitic carbon as promising insertion anode for sodium ion battery with long cycle life - Suryawanshi, Anil; Mhamane, Dattakumar; Nagane, Satyawan; Patil, Shankar; Aravindan, Vanchiappan; Ogale, Satishchandra; Srinivasan, Madhavi (Electrochimica Acta, 2014)
We report facile, one step synthesis of disordered graphitic carbon by high temperature (1000 degrees C) pyrolysis of indanthrone dye (ID). The pyrolysed carbon is disordered in nature and the same is clearly evidenced by various analytical techniques like X-ray diffraction, Raman spectroscopy and high resolution transmission electron microscopy. Na-insertion properties of such indanthrone dye derived disordered graphitic carbon (IDDGC) is evaluated in half-cell assembly (Na/IDDGC). The test cell delivered a reversible capacity of similar to 160 mAh g(-1) at current density of 25 mAg 1. In addition, excellent cycling profiles are noted for such IDDGC, which retains 67% of initial reversible capacity after 500 cycles. The present study clearly highlights the importance of disorder in the graphitic carbon for efficient Na-ion storage. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: anode; disordered carbon; indanthrone; Na-ion battery

MOF-derived crumpled-sheet-assembled perforated carbon cuboids as highly effective cathode active materials for ultra-high energy density Li-ion hybrid electrochemical capacitors (Li-HECs) - Banerjee, Abhik; Upadhyay, Kush Kumar; Puthusseri, Dhanya; Aravindan, Vanchiappan; Madhavi, Srinivasan; Ogale, Satishchandra (Nanoscale, 2014)
Lithium ion hybrid capacitors (Li-HECs) have attracted significant attention for use in next generation advanced energy storage technologies to satisfy the demand of both high power density as well as energy density. Herein we demonstrate the use of very high surface area 3D carbon cuboids synthesized from a metal-organic framework (MOF) as a cathode material with Li4Ti5O12 as the anode for high performance Li-HECs. The energy density of the cell is similar to 65 W h kg(-1) which is significantly higher than that achievable with commercially available activated carbon (similar to 36 W h kg(-1)) and a symmetric supercapacitor based on the same MOF-derived carbon (MOF-DC similar to 20 W h kg(-1)). The MOF-DC/Li4Ti5O12 Li-HEC assembly also shows good cyclic performance with similar to 82% of the initial value (similar to 25 W h kg(-1)) retained after 10 000 galvanostatic cycles under high rate cyclic conditions. This result clearly indicates that MOF-DC is a very promising candidate for future P-HEVs in a Li-HEC configuration.

Oligomer-salt derived 3D, heavily nitrogen doped, porous carbon for Li-ion hybrid electrochemical capacitors application - Gokhale, Rohan; Aravindan, Vanchiappan; Yadav, Prasad; Jain, Srashti; Phase, Deodatta; Madhavi, Srinivasan; Ogale, Satishchandra (Carbon, 2014)
3D high surface area porous carbon is seen to form via self assembly of porous graphene sheets by direct pyrolysis of an oligomer salt tailored for the realization of molecular level activation. The oligomer salt was derived from 4-amino benzoic acid as the monomer by a facile free radical polymerization process. Incorporation of the functional groups (-COONa) eliminate the need for any external activating agents (KOH, ZnCl2, etc.) and also render high degree of sub-nanoscale homogeneity. This oligomer derived carbon (ODC) exhibits efficient performance in non-aqueous charge storage application namely Li-ion hybrid electrochemical capacitor (Li-HEC) owing to its high surface area, 3D interconnectivity and an appropriate pore size distribution. The Li-HEC fabricated with ODC based electrodes delivered a maximum energy density of similar to 63 Wh kg(-1) with spinel L4Ti5O12 as the anode. (C) 2014 Elsevier Ltd. All rights reserved.

High surface area porous carbon for ultracapacitor application by pyrolysis of polystyrene containing pendant carboxylic acid groups prepared via click chemistry - Chhatre, Shraddha; Aravindan, Vanchiappan; Puthusseri, Dhanya; Banerjee, Abhik; Madhavi, Srinivasan; Wadgaonkar, Prakash P.; Ogale, Satishchandra B. (Materials Today Communications, 2015)

3D interconnected porous graphene sheets loaded with cobalt oxide nanoparticles for lithium-ion battery anodes - Puthusseri, Dhanya; Aravindan, Vanchiappan; Madhavi, Srinivasan; Ogale, Satishchandra (Energy Technology, 2016)
Nanomaterials with high surface-to-volume ratio and tunable electronic and optical properties have expanded their use in variety of applications, especially energy conversion and storage. Here we report on the synthesis of a cobalt oxide (Co3O4)/3D-interconnected porous graphene (PG) nanocomposite by using a simple solvothermal route and its application as a Li-ion battery anode. Among the different compositions investigated, the composite PG-600 (with 50% PG) showed a discharge capacity of 700mAhg(-1) at a current density of 500mAg(-1) and maintained 90% retention after 80cycles. The high surface area of the 3DPG sheets helps the Co3O4 nanoparticles to form a uniform dispersion on the surfaces. The increased surface area (accessibility) and electrical conductivity of the composite result in significant enhancement in the capacity, cycling stability, and rate capability than the native Co3O4 phase.
Keywords: Cobalt oxide; Energy storage; graphene; lithium-ion batteries; Nanocomposites

Graphene based nanocomposites for alloy (SnO2), and conversion (Fe3O4) type efficient anodes for Li-ion battery applications - Mhamane, Dattakumar; Aravindan, Vanchiappan; Taneja, Divya; Suryawanshi, Anil; Game, Onkar; Srinivasan, Madhavi; Ogale, Satishchandra B. (Composites Science and Technology, 2016)
Two types of trigol reduced one pot synthesized graphene (TRG) based nanocomposites (SnO2-TRG, and Fe3O4-TRG) are examined as potential anodes for Lithium ion battery (LIB) applications. The two specific systems represent different electrode reaction mechanisms, namely alloying, and conversion respectively. The high resolution transmission electron microscopy (HR-TEM) analysis confirms the uniform distribution of SnO2 (similar to 2 nm), and Fe3O4 (similar to 8 nm) particulates on ultrathin TRG nanosheets and highlights the importance of surfactant free synthesis. The SnO2-TRG, and Fe3O4-TRG exhibited the maximum reversible capacity of similar to 947, and similar to 1024 mA h g(-1), respectively. The results show that such graphene based composite materials can be effectively used as prospective anodes for LIB applications. (C) 2016 Elsevier Ltd. All rights reserved.

Red mud and li-ion batteries: a magnetic connection - Suryawanshi, Anil; Aravindan, Vanchiappan; Madhavi, Srinivasan; Ogale, Satishchandra B. (Chemsuschem, 2016)
Exceptional Li-ion battery performance is presented with the oxide component of the anode was extracted from red mud by simple magnetic separation and applied directly without any further processing. The extracted material has -Fe2O3 as the major phase with inter-dispersed phases of Ti, Al, and Si oxides. In a half-cell assembly, the phase displayed a reversible capacity (approximate to 697mAhg(-1)) with excellent stability upon cycling. Interestingly, the stability is rendered by the multiphase constitution of the material with the presence of other electrochemically inactive metal oxides, such as Al2O3, SiO2, and Fe2TiO4, which could accommodate the strain and facilitate release during the charge-discharge processes in the electrochemically active maghemite component. We fabricated the full-cell assembly with eco-friendly cathode LiMn2O4 by adjusting the mass loading. Prior to full-cell assembly, an electrochemical pre-lithiation was enforced to overcome the irreversible capacity loss obtained from the anode. The full-cell delivered a capacity of approximate to 100mAhg(-1) (based on cathode loading) with capacity retention of approximate to 61% after 2000cycles under ambient conditions.